(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze in depth the implementation of library facility maintenance at MI Ma’ariful Ulum, covering aspects of awareness-building, understanding, organization, implementation, and documentation. This study employs a qualitative approach with a phenomenological research design, focusing on understanding experiences and real practices in library facility maintenance activities. The research subjects consisted of 13 people, including the principal, the vice principal for facilities and infrastructure, the librarian, teachers, and students. Data collection techniques include interviews, observations, and documentation, while data analysis is conducted through stages of data reduction, data display, and conclusion drawing, with data validity tested using source and technique triangulation. The results indicate that the maintenance of library facilities has been carried out fairly well through habituation in maintaining cleanliness, providing understanding to school members, task distribution involving various parties, implementation of routine maintenance activities, and documentation through inventory books. However, maintenance activities are still relatively simple, not yet based on a preventive schedule, and the documentation system is still conducted manually. Therefore, it is necessary to develop a more structured system and utilize technology to improve the effectiveness of library facility maintenance